Malaria in Turkey: A comprehensive analysis of diagnosis, treatment, and the impact of COVID-19, ten years after malaria elimination (2012-2023) - Sahin, Ozguen Ekin; Kalay, Zeynepguel; Sari, Nagehan Didem; Baurel, Ayse; Ersoz, Guelden; Ertem, Guenay Tuncer; Ergonul, Onder (Elsevier Sci Ltd, 2025)
Background: The characteristics, diagnosis, and treatment stages of malaria in Turkey in the last ten years are not known except few case reports. We aimed to describe the details of the diagnosis and treatment practices of malaria cases in various hospitals across Turkey between 2012 and 2023 after the declaration of the elimination of malaria. Methods: We collected the patient data from 30 centers by using Qualtrics Survey Software. The patients were categorized according to the WHO Malaria Severe Disease Symptoms guidelines. Results: We detected 299 malaria cases. Of these patients, 23.7 % experienced misdiagnosis, with 77.5 % of misdiagnosed cases receiving antibiotics. Among the patients, 9 (3 %) had no travel history. Additionally, 28 (9.4 %) patients required admission to the intensive care unit (ICU) during hospitalization. There is a significant association between misdiagnosis and subsequent ICU admissions. Additionally, the duration between malaria diagnosis and the initiation of treatment significantly affected ICU admissions. Furthermore, the number of cases with severe malaria (according to WHO criteria) and ICU admissions increased after the COVID-19 period. In multivariate analysis, initial misdiagnosis was found to be associated with ICU admission (OR: 2.8, p < 0.05), while each day's treatment delays post-diagnosis increased ICU admissions (OR: 1.26, p < 0.05). Conclusion: Misdiagnosis is common which delays the treatment and is correlated with higher admissions to ICUs. Post-COVID-19, there was a notable increase in both ICU admissions and cases of severe malaria, suggesting an escalation in disease severity that warrants further investigation. The resurgence of rare malaria cases with no travel history to abroad highlights the necessity of continued vigilance for new malaria cases. Efforts to promptly treat upon diagnosis and improve diagnostic accuracy in Turkey, where malaria is uncommon, are crucial. Enhancing diagnostic methods and treatment strategies remains essential, especially in significant events like COVID-19.
Keywords: Epidemiology